A review of metal injection moulding on WC-Co cemented carbide comprised of Grain Growth Inhibitors (GGI) - Khairudin, Siti Nur Fatimah; Pahroraji, Hazriel Faizal; Alias, Siti Khadijah; Ibrahim, Mohd Halim Irwan (Penerbit UTHM, 2022)
This paper aims to provide a summary of metal injection moulding technologies utilising cemented WCCo carbides comprised of grain growth inhibitors (GGI). The advanced manufacturing of metal injection moulding (MIM) has the ability to produce cement nanostructured carbides. In addition, the nature of the feedstock plays a crucial role when manufacturing a defect-free component at each point of the MIM phase, thus the interactions between the metal powder and the binder combining, moulding, and debinding are important to be recognised. The primary objective of this analysis is to investigate the characterization of feedstock to form a homogenous mixture. There are five criteria to classify features of the feedstock which include powder characteristics, binder composition, powder content ratio, mixing cycle, and approaches to palletization. Not only that, the feedstock must meet specific criteria; higher powder loading with excellent flowability by the rheological approaches. The second goal of the research is to re-evaluate feedstock’s flow properties in relation to rheological activity in terms of index flow behaviour (n), activation energy (E), and mouldability (α). MIM practitioners have continued to underestimate erratic product quality, including inadequate regulation, distortion, and internal and external defects. These defects can arise in the early processing phases, but often occur only after sintering or debinding. The approaches are also challenging to provide. This chapter includes a description of MIM defects. Explanations are listed and recommendations are provided for these defects.